Stratified Approaches to Antiplatelet Therapies Based on Platelet Reactivity Testing - Ostrowska, Małgorzata; Kubica, Jacek; Adamski, Piotr; Kubica, Aldona; Eyileten, Ceren; Postula, Marek; Toma, Aurel; Hengstenberg, Christian; Siller-Matula, Jolanta M. (Frontiers in Cardiovascular Medicine, 2019)
Antiplatelet therapy with P2Y12 receptor inhibitors (clopidogrel, prasugrel, ticagrelor, cangrelor) is a cornerstone of medical therapy after percutaneous coronary interventions. Significant prevalence of hHigh on-treatment platelet reactivity (HTPR) under on clopidogrel treatment led to introduction of more potent P2Y12 inhibitors: prasugrel (a third generation thienopyridine), ticagrelor and cangrelor (cyclopentyl-triazolo-pyrimidines). Nevertheless, the more potent platelet inhibition and resulting low on-treatment platelet reactivity (LTPR) has led to increased risk of major bleeding events. These limitations resulted in a need for an individualized antiplatelet therapy approach. In this review, we describe a stratified approach for use of antiplatelet therapies, which incorporates patient’s demographical and biological data to maximise efficacy while minimizing bleeding risks. This review furthermore discusses the current role and future perspectives of diagnostic tools such as platelet function testing to optimize antiplatelet therapy with a focus on deescalating therapies to reduce bleeding risks.